1991
DOI: 10.1073/pnas.88.6.2189
|View full text |Cite
|
Sign up to set email alerts
|

Binding of soluble CD4 proteins to human immunodeficiency virus type 1 and infected cells induces release of envelope glycoprotein gp120.

Abstract: Human immunodeficiency virus (HIV) infects cells after binding of the viral envelope glycoprotein gpl20 to the cell surface recognition marker CD4. gpl20 is noncovalently associated with the HIV transmembrane envelope glycoprotein gp4l, and this complex is believed responsible for the initial stages of HIV infection and cytopathic events in infected cells. Soluble constructs of CD4 that contain the gpl20 binding site inhibit HIV infection in vitro. This is believed to occur by competitive inhibition ofviral bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
136
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(143 citation statements)
references
References 42 publications
7
136
0
Order By: Relevance
“…The differential loss of gp120 between X4-and R5-tropic HIV-1 may be due to differences in the inherent stability of the gp120-gp41 complex, or to differences in gp120 conformational changes induced upon CD4 binding. Previous studies have shown that laboratoryadapted strains of HIV-1, which are generally X4-tropic, readily shed gp120 upon addition of soluble CD4 and are more sensitive to inhibition by sCD4 (31,36,50,61). The preferential inhibition of X4-tropic HIV-1 by sCD4 is also in general agreement with the hypothesis that cellular CD4 is more detrimental for replication of X4-tropic HIV-1.…”
Section: Discussionsupporting
confidence: 77%
“…The differential loss of gp120 between X4-and R5-tropic HIV-1 may be due to differences in the inherent stability of the gp120-gp41 complex, or to differences in gp120 conformational changes induced upon CD4 binding. Previous studies have shown that laboratoryadapted strains of HIV-1, which are generally X4-tropic, readily shed gp120 upon addition of soluble CD4 and are more sensitive to inhibition by sCD4 (31,36,50,61). The preferential inhibition of X4-tropic HIV-1 by sCD4 is also in general agreement with the hypothesis that cellular CD4 is more detrimental for replication of X4-tropic HIV-1.…”
Section: Discussionsupporting
confidence: 77%
“…Dynamic and sequential interactions occur between viral and cellular proteins after the binding of gp120 to the CD4 receptor. Soluble CD4 enhanced gp120 shedding from infected cell surfaces (1,12), while on the other hand, anti-V3 monoclonal antibodies bound more efficiently to soluble CD4-treated cells (21). The above findings indicate the conformational changes of gp120 after its binding to the CD4 molecule.…”
Section: Introductionsupporting
confidence: 49%
“…Similarly, m-58 DEC 97 dissociation of gpl20 by CD4 is accompanied by exposure of epitopes on gp41 that are not reactive in the native molecule (Hart et al, 1991;Sattentau and Moore, 1991). Epitope exposure is not dependent upon loss of gpl20 since similar results were obtained following CD4 binding at 4° C Sattentau et al, 1995).…”
Section: Immune Responses To Gp41supporting
confidence: 68%
“…Dissociation was temperature dependent and no significant dissociation of gpl20 was observed between 4° C and 16° C (Hart et al, 1991;Moore and Klasse, 1992;Moore et al, 1991;Sattentau and Moore, 1991).…”
Section: Immune Responses To Gp41mentioning
confidence: 99%